Enhancing Gonococcal Antimicrobial Resistance Surveillance in Cisgender Women, Strengthening the US Response to Resistant Gonorrhea, 2018 to 2019. Issue 12 (2nd December 2021) - Wendel, Karen A.; Mauk, Kerry; Amsterdam, Lori; McNeil, Candice J.; Pfister, John R.; Mobley, Victoria; Mettenbrink, Christie; Nishiyama, Masayo; Terrell, Erica; Baldwin, Tamara; Pham, Cau D.; Nash, Evelyn E.; et al.
Abstract : Three jurisdictions funded under the Centers for Disease Control and Prevention's Strengthening the US Response to Resistant Gonorrhea project increased gonococcal antimicrobial resistance surveillance in cisgender women. Abstract : Background: Cisgender women have been underrepresented in antibiotic-resistant gonorrhea (ARGC) surveillance systems. Three of 8 project sites (City of Milwaukee [MIL], Guilford County [GRB], Denver County [DEN]), funded under the Centers for Disease Control and Prevention's Strengthening the US Response to Resistant Gonorrhea (SURRG), focused efforts to better include cisgender women in ARGC surveillance. Methods: MIL, GRB, and DEN partnered with diverse health care settings and developed gonorrhea culture criteria to facilitate urogenital specimen collection in cisgender women and men. Regional laboratories within the Antibiotic Resistance Laboratory Network performed agar dilution antibiotic susceptibility testing (AST) of gonococcal isolates. Data from 2018 and 2019 were analyzed. Results: In SURRG, 90.5% (11, 464 of 12, 667) of the cisgender women from whom urogenital culture specimens were collected were from MIL, GRB, and DEN. Of women in SURRG whose gonococcal isolates underwent AST, 70% were from these 3 sites. In these 3 sites, a substantial proportion of cisgender women with positive urogenital cultures and AST were from health care settings other than sexually transmitted disease (STD) clinics (non-STD clinics; MIL, 56.0%; GRB, 80.4%; and DEN, 23.5%). Isolates with AST were obtained from 5.1%, 10.2%, and 2.4% of all diagnosed gonorrhea cases among cisgender women in MIL, GRB, and DEN, respectively, and were more often susceptible to all antibiotics than those from cisgender men from each of these sites. Conclusions: With focused efforts and partnerships with non-STD clinics, 3 SURRG sites were able to include robust ARGC surveillance from cisgender women. These findings may guide further efforts to improve gender equity in ARGC surveillance.